Altos índices de radiación ultravioleta en Medellín y en una localidad del oriente antioqueño (COLOMBIA) (2010)
ABSTRACT: The incidence of skin cancer has risen in the last two decades worldwide. Cumulative and long-term solar ultraviolet (UV) exposure is one of the most important risk factors for melanoma, non-melanoma skin cancer and cataracts. The UV Index (UVI) has been designed to educate the general population regarding sun exposure and the risk for skin cancer. Objective: To quantify the UVI in two different cities in the province of Antioquia (Colombia). Results: High UVI´s (Mean: 10) were found in the northeast region of Antioquia as well as in its capital, Medellin city. Discussion and conclusions: This particular population appeared to be exposed to high levels of UV Radiation (UVR) all year round. The use of the UVI may be a useful educative tool for the community in regards to the health risks of overexposure to UVR.